2012
DOI: 10.1080/08856257.2012.711960
|View full text |Cite
|
Sign up to set email alerts
|

The shifting role of the special needs assistant in Irish classrooms: a time for change?

Abstract: The education of pupils with special educational needs in Ireland has generally been influenced by national and international inclusion policy and legislation so that the majority of these children now take their place alongside peers in mainstream classrooms. In Ireland, a support network comprising the teacher and additional classroom assistance now characterises much inclusive school provision. Such support is often provided via learning support teachers, resource teachers and special needs assistants (SNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
(56 reference statements)
2
21
0
Order By: Relevance
“…The results of research also suggest that the TAs are performing significant pedagogical, assessment, socialization and behavioural roles (Carter et al, 2008;Groom & Rose, 2006;Healy, 2011;Howard & Ford, 2007;Keating & O'Connor, 2012;Liston et al, 2009;Wasburn-Moses et al, 2013;, and making important decisions about the educational programs of students with disabilities (Cameron, 2014;Liston et al, 2009). For instance, Giangreco and Broer (2005) found that the majority of TAs surveyed reported that they make teaching and curricular decisions without consulting teachers.…”
Section: Research Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of research also suggest that the TAs are performing significant pedagogical, assessment, socialization and behavioural roles (Carter et al, 2008;Groom & Rose, 2006;Healy, 2011;Howard & Ford, 2007;Keating & O'Connor, 2012;Liston et al, 2009;Wasburn-Moses et al, 2013;, and making important decisions about the educational programs of students with disabilities (Cameron, 2014;Liston et al, 2009). For instance, Giangreco and Broer (2005) found that the majority of TAs surveyed reported that they make teaching and curricular decisions without consulting teachers.…”
Section: Research Questionmentioning
confidence: 99%
“…Brown and Stanton-Chapman (2014) found that the roles of TAs vary based on the setting, motivation of the TAs, and the receptivity of the teachers. The roles performed by TAs also appear to be affected by teachers and TAs having differing views of the roles of TAs in inclusive classrooms (Keating & O'Connor, 2012), with TAs viewing their primary roles as providing academic support to students with disabilities and teachers identifying the primary roles of TAs as aiding teachers in delivering instruction and managing student behaviour (Butt & Lowe, 2012). Appl (2006) concluded that age as well as experiential and philosophical differences are factors that impact the relationships between beginning teachers and TAs.…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers and assistants have mentioned difficulties at the beginning of cooperation associated with a lack of teachers' experience in the environment of secondary schools and insufficient communication between teachers and assistants (Bartoňová & Pipeková, 2008;Giangreco & Doyle, 2007;Keating & O'Connor, 2012;Kratochvílová, 2013;Němec & Štěpařová, 2008;Webster et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Keating and O'Connor (2012) found that almost 50% of the assistants and cooperating teachers in Ireland did not have any dedicated time for simultaneous lesson planning in their timetable and that more than 60% of assistants are not invited to teacher meetings or similar teachers' meeting.…”
Section: Cooperation Between Assistant and Teachermentioning
confidence: 99%